Plan estratégico para la compañía equipo petrolero s.a. del cantón Francisco de Orellana, provincia de Orellana, para el periodo 2017- 2021 - Andi Grefa, Maritza Elizabeth (2017)
he present research work has as general objective: To propose a strategic plan for the company Equipo Petróleo S.A. Of the Canton Francisco de Orellana, Province of Orellana, for the period 2017-2021, which will be of great help to the knowledge of the organizational situation and to make decisions that lead to the continuous improvement of the company. To develop the research work the following specific objectives were proposed: Carry out an internal situational diagnosis of the company through a survey and interview to the managers that allows to determine strengths and weaknesses of the organization. Analyze the current situation of the company by means of information crossing, using the SWOT matrix to determine the strategic objectives. Perform a SWOT. Design the business philosophy: Mission, vision, objectives, principles and values, to determine the horizon of the company. Implement a CIM for monitoring and control. To carry out an institutional POA for the accomplishment of the objectives To meet the objectives we used the analytical, deductive, inductive, scientific and technical methods such as: observation, interview, survey that helped us diagnose the situation of the company Equipo Petrolero S.A. In the results, the surveys of the 25 employees and the 5 clients of Equipo Petrolero SA were tabulated. In order to diagnose the current situation of the company, the internal and external aspects of the company were analyzed, opportunities, threats, strengths and weaknesses were formulated, and the SWOT matrix was designed where the strategic objectives were determined with the respective proposals. The strategic objectives proposed the following: Develop short and long term goals; Design business philosophy such as mission, mission and values; Motivate and encourage employees, so their performance is efficient and effective in their daily work; Avoid the departure of the staff that already takes time working for the company. Finally the respective conclusions and memories are realized, with the study realized will be a great help for the company Equipo Petrolero S.A.